Mind mapping tool increased critical thinking through blended learning - Fitria, Yunike Juniarti; Floriasti, Tri Wahyuni; Djohan, Dr; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: The process of learning creates interaction and coordination and finding solution. Students who are engaged in that process will find themselves useful as they have shared ideas. Sharing ideas is a significant part. Aims and Objective: This study aims to describe the application of mind mapping in music learning as an effort to increase students' critical thinking. It has not been commonly applied in practical music learning processes. Materials and Methods: This research was conducted with a total of 75 students of music education who took violin subject. Initially, they discussed the issue that related with a song, and it was followed by mind mapping to find the ideas. Results: Through this process, students are expected to get a comprehensive understanding, and obtain effectively relevant guidelines regarding the material that must be trained. Conclusion: Exceedingly students can generate critical thinking, which later give influence in song interpretation.